Tiga Unsur Pembangunan Desa di Negeri Rumah Tiga Kecamatan Teluk Ambon Kota Ambon - Patty, Julia Theresia; Ponto, Iriane Sosiawaty; Soselisa, Pieter Sammy; Alhamid, Rugayah; Rahanra, Ivonny Yeany; Sakir, Ahmad Rosandi (Lok Seva: Journal of Contemporary Community Service, 2023)
The development of the village is basically the entire process of organizing a series of planned and systematic activities carried out by the village government together with the entire community in various aspects of life, including social, cultural, economic, and political fields, to improve the village's quality of life from an unfavorable state to a perceived better one in the future. The methods used in this Community Service activity include discussions, question-and-answer sessions, and opinions sharing. The results of this Community Service activity are activities dedicated to the community, with discussions about the three development elements present in the Negeri Rumah Tiga Kota Ambon. This provides an overview of how the development of the capabilities of the local population/community and the preparation of mechanisms as the main actors in development are nurtured, ensuring that development proceeds by the established programs.